Group Counseling with Motivational Interviewing Approach to Enhance Intrinsic Motivation and Academic Engagement - Nurhidayat, Arie Ichwan; Mulawarman, Mulawarman; Sunawan, Sunawan (Jurnal Kajian Bimbingan dan Konseling, 2024)
The objective of this study was to assess the efficacy of motivational interviewing (MI) group counseling in enhancing intrinsic motivation and academic engagement among students at State Senior High School 2 Sragen, Indonesia. Students with low intrinsic motivation and academic engagement often display a lack of attention during learning activities, disinterest in school, use of cell phones for non-academic purposes during study time, and failure to complete assigned tasks. This study employed a pretest and multiple posttest design, with 14 students selected via purposive sampling and subsequently divided into two groups: the experimental group (7 students), who received group counseling with the MI approach over four meetings; and the control group (7 students), who did not receive intervention. Data were collected using the Intrinsic Motivation Scale (α = 0.92) and the Academic Engagement Scale (α = 0.89). The data were analyzed using the mixed MANOVA technique. Results demonstrated that the MI approach group counseling intervention positively influences students' intrinsic motivation and academic engagement. Additionally, a measurement effect (time) was observed in relation to students' intrinsic motivation and academic engagement. The study also showed an interaction effect between the MI approach group counseling intervention and measurement (time) on students' intrinsic motivation and academic engagement. Therefore, MI approach group counseling is an effective method for increasing students' intrinsic motivation and academic engagement. The presence of ambivalence is a crucial aspect in group counseling with the MI approach to facilitate the desired change talk.